Political Dynamics and Challenges of Local Elections 2024 in Bulukumba Regency, Indonesia - Noer Arfah, Iqbal; Junaedi, Junaedi; Mustari, Nuryanti (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
This study analyzes political dynamics in Bulukumba Regency's 2024-2029 Simultaneous Regional Elections, examining candidate branding strategies, political party gatekeeping via B1-KWK recommendations (letter of mutual agreement), and comparative electoral patterns. A critical phenomenon emerged when party cadres were denied nominations by their own parties and defected to incumbent Andi Muhtar Ali Yusuf, revealing strategic loyalty fractures. Using a descriptive qualitative approach with in-depth interviews (N=25), direct observation, and document analysis, findings demonstrate: (1) incumbent dominance anchored by Muhtar’s branding as